Más allá de la Capacidad Estatal: Sociedad Civil e Implementación de Políticas a Nivel Subnacional en Cusco y San Martín (Perú) - Eduardo Dargent; Stephanie Rousseau; María Claudia Augusto (Colombia Internacional, 2017)
In this article we present two cases that highlight how regional civil society contributes to improving the implementation of regulations and public policies in subnational spaces. In the regions of San Martín and Cusco in Peru, civil society actors took advantage of decentralized space to effectively enforce national laws (environmental regulations in the first case, and rights for the population that speaks indigenous languages in the second). These cases help to explain the heterogeneity encountered in implementating regulations in subnational spaces, a common phenomenon in Latin America.